Glanzmann`s Thrombosthenia: A rare cause of Recurrent Epistaxis - Khalid, Abdul; Baqai, Tariq; Bukhari, Murtaza (International Journal of Pathology, 2018)
Platelets play an important role in the process of homeostasis in endothelial injuries. Glanzmann`sthrombasthenia is very rare inherited functional disorder of platelets. It is characterized by failure ofplatelet aggregation due to the lack of cell membrane glycoproteins IIb/ IIIa. It presents with bleedingin young age. The bleeding episodes are usually mild and recurrent but sometimes bleeding may besevere enough to be life threatening. The platelets are the first major component of coagulation systemat the site of injury and bleeding. In case of trauma platelets adhere to the exposed sub-endothelial tissue.Platelets release biochemical mediators (Adenosine biphosphate and serotonin) and more cells arerecruited towards the injured area in a process called activation of platelets. We report a twelve yearsold boy with recurrent epistaxis where nasal packing was ineffective to control bleeding. His bleedingprofile showed significantly prolonged bleeding time and platelet function studies confirmed the diagnosis.He was managed with platelet transfusions